Embedded real-time multi-baseline stereo - Honegger, Dominik; Sattler, Torsten; Pollefeys, Marc (2017 International Conference on Robotics and Automation (ICRA), 2017)
Dense depth map estimation from stereo cameras has many applications in robotic vision, e.g., obstacle detection, especially when performed in real-time. The range in which depth values can be accurately estimated is usually limited for two-camera stereo setups due to the fixed baseline between the cameras. In addition, two-camera setups suffer from wrong depth estimates caused by local minima in the matching cost functions. Both problems can be alleviated by adding more cameras as this creates multiple baselines of different lengths and since multi-image matching leads to unique minima. However, using more cameras usually comes at an increase in run-time. In this paper, we present a novel embedded system for multi-baseline stereo. By exploiting the parallelization capabilities within FPGAs, we are able to estimate a depth map from multiple cameras in real-time. We show that our approach requires only little more power and weight compared to a two-camera stereo system. At the same time, we show that our system produces significantly better depth maps and is able to handle occlusion of some cameras, resulting in the redundancy typically desired for autonomous vehicles. Our system is small in size and leight-weight and can be employed even on a MAV platform with very strict power, weight, and size requirements.